Enhanced near infrared persistent luminescence of Zn2Ga2.98Ge0.75O8:Cr0.023+ nanoparticles by partial substitution of Ge4+ by Sn4+. Issue 20 (19th March 2018) - Song, Ting; Zhang, Meng; Liu, Yuxue; Yang, Jian; Gong, Zheng; Yan, Hong; Zhu, Hancheng; Yan, Duanting; Liu, Chunguang; Xu, Changshan
Abstract : Distance between the 4 T2 energy level and traps depth can be modulated and the NIR persistent luminescence can be enhanced. Abstract : Spinel-phase Zn2 Ga2.98 Ge0.75– x Sn x O8 :Cr0.02 3+ (ZGGSO:Cr 3+ ) nanoparticles with various Sn 4+ concentrations were prepared by a hydrothermal method in combination with a post-annealing in vacuum at high temperature. For these nanoparticles, the observed near infrared (NIR) persistent luminescence peaked at ∼697 nm and originates from the 2 E, 4 T2 ( 4 F) → 4 A2 transitions of Cr 3+ and the afterglow time exceeds 800 min. For both the interior and surface Cr 3+ ions in the ZGGSO host, it can be found that the increased energy transfer from Cr 3+ to the deep trap (anti-site defects, ) after the substitution of Ge 4+ by Sn 4+ plays a key role in enhancing the persistent luminescence of the ZGGSO:Cr 3+ nanoparticles. Strikingly, this energy transfer process can be controlled through the variations in the crystal field strength and the trap depths. Our results suggest that not only Sn 4+ substitution can improve in vivo bioimaging but also the existence of deep traps in ZGGSO:Cr 3+ nanoparticles is helpful for retracing in vivo bioimaging at any time.